Intratracheal transplantation of human umbilical cord blood-derived mesenchymal stem cells attenuates Escherichia coli-induced acute lung injury in mice - Kim Eun; Chang Yun; Choi Soo; Kim Jin; Yoo Hey; Ahn So; Sung Dong; Kim Soo; Park Ye; Park Won (Respiratory Research, 2011)
Abstract Background Human umbilical cord blood (UCB)-derived mesenchymal stem cells (MSCs) attenuate hyperoxic neonatal lung injury primarily through anti-inflammatory effects. We hypothesized that intratracheal transplantation of human UCB-derived MSCs could attenuate Escherichia coli (E. coli)-induced acute lung injury (ALI) in mice by suppressing the inflammatory response. Methods Eight-week-old male ICR mice were randomized to control or ALI groups. ALI was induced by intratracheal E. coli instillation. Three-hours after E. coli instillation, MSCs, fibroblasts or phosphate-buffered saline were intratracheally administered randomly and survival was analyzed for 7 days post-injury. Lung histology including injury scores, myeloperoxidase (MPO) activity, and protein levels of interleukin (IL)-1α, IL-1β, IL-6, tumor necrosis factor (TNF)-α, and macrophage inflammatory protein (MIP)-2 as well as the wet-dry lung ratio and bacterial counts from blood and bronchoalveolar lavage (BAL) were evaluated at 1, 3, and 7 days post-injury. Levels of inflammatory cytokines in the lung were also profiled using protein macroarrays at day 3 post-injury which showed peak inflammation. Results MSC transplantation increased survival and attenuated lung injuries in ALI mice, as evidenced by decreased injury scores on day 3 post-injury and reduced lung inflammation including increased MPO activity and protein levels of IL-1α, IL-1β, IL-6, TNF-α, and MIP-2 on day 3 and 7 post-injury. Inflammatory cytokine profiles in the lungs at day 3 post-injury were attenuated by MSC transplantation. MSCs also reduced the elevated lung water content at day 3 post-injury and bacterial counts in blood and BAL on day 7 post-injury. Conclusions Intratracheal transplantation of UCB-derived MSCs attenuates E. coli-induced ALI primarily by down-modulating the inflammatory process and enhancing bacterial clearance.